45.2: Long Lifetime Electron Transporting Materials for AMOLED. (4th October 2019) - Huang, Heh-Lung; Chao, Teng-Chih; Sun, Jie; Lin, Chi-Jen
Abstract : A series of new electron transporting materials with good thermal stability were designed and developed. The devices of this ET‐1 applied in top fluorescent blue devices, top green phosphorescent device and top phosphorescent red device, exhibited high efficiency and long lifetime with blue index of 162 and the LT95 lifetime is around 2100 h under 500 cd/m 2 .